Small vessel vasculitis associated with culture-negative infective endocarditis related to a cardiac device: a case report. Issue 8 (2nd August 2022) - El-Gaaly, Maged; Tomlinson, James Steven; Ezzo, Talal
Abstract: Background: Culture-negative endocarditis is uncommon, occurring in less than a third of all cases of infective endocarditis (IE). Culture-negative IE related to a cardiac device is an even greater diagnostic challenge due to its insidious presentation, with onset of symptoms ranging between 3 and 12 months after device implantation. Sensitivity of the modified Duke's criteria remains low in culture-negative and cardiac device-related IE (CDRIE) since classical signs and symptoms of IE are often absent. Small vessel vasculitis has been reported as an immune response to IE. Recognizing immunological phenomenon related to IE is of paramount clinical importance, prompting the search for an underlying infection and avoiding the use of immunosuppressive medications which would otherwise result in an adverse outcome. Case summary: An 81-year-old Caucasian male presented to the ambulatory medical unit with a two-week history of a symmetrical, generalized purpuric rash. He had an indwelling permanent pacemaker following a transcatheter aortic valve implantation for severe aortic stenosis five years ago. Blood tests showed an iron deficiency anaemia, thrombocytopenia and normal renal function, both CRP and ESR were raised at 61  and 30 mm/hr, respectively. Skin biopsy demonstrated small vessel cutaneous vasculitis. Transthoracic echocardiography revealed a mobile mass measuring 0.9 × 1.7 cm, confirmed on transoesophageal echocardiogram as pacing lead endocarditis. Blood cultures were persistently negative. The patient underwent pacemaker lead extraction, following which the vasculitic rash improved. Discussion: Blood cultures in IE are more likely to be negative if there is a prior antibiotic administration or causative micro-organisms with limited proliferation which fail to grow in conventional media conditions. Transesophageal echocardiography (TOE) offers improved sensitivity and diagnostic yield when compared to transthoracic echocardiography (TTE) in patients with a high clinical suspicion of CDRIE. The evidence in the literature describing culture-negative IE associated with small vessel vasculitis is limited. However, it is recognized that cutaneous small vessel vasculitis may be associated with an underlying bacterial infection. IE produces an inflammatory response, resulting in the deposition of circulating immune complexes and cutaneous signs which are included in the modified Duke's criteria to aid diagnosis. Management of CDRIE requires a multi-disciplinary team approach with an 'Endocarditis Team.' Pacemaker lead infection requires transvenous lead extraction if it is a newly implanted lead. Locking stylets, extraction sheaths or snare retrieval are usually required in cases of older implanted leads. Surgical lead extraction remains the gold standard for larger vegetations (>20 mm) or associated valve endocarditis.